A resistive circumferential ablation zoned coating and method of making same
Patent Information
- Application Number
- CN202410493375.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-04-23
AI Technical Summary
[0005]本发明的目的在于提供一种抗循环烧蚀分区涂层及其制备方法,用以解决热结构件在服役过程中不同区域因变形不均匀而产生较大热应力的技术问题
[0025]本发明公开了一种抗循环烧蚀分区涂层的制备方法,在基体材料表面先制备SiC内涂层,随后在SiC内涂层分区制备(Hf,Ta)B2-SiC分区涂层,随后依次进行热处理和高温气相渗硅处理,最终在基体材料表面形成一种抗循环烧蚀分区涂层((Hf,Ta)B2-SiC分区涂层);该方法能够根据基体材料实际服役过程中表面不同区域的服役环境差异,对基体材料表面涂层进行分区结构设计,根据不同区域的服役环境差异,制备不同比例的(Hf,Ta)B2-SiC-酚醛树脂料浆,制备得到的抗循环烧蚀分区涂层沿基体材料径向成梯度变化,即随着距试样中心距离增大,(Hf,Ta)B2陶瓷相的含量逐渐减小,SiC含量逐渐增加,可实现试样表面不同区域耐高温性能的调控,并能够有效缓解涂层不同区域因变形不均匀从而产生的应力,提高涂层的抗循环烧蚀性能。
Smart Images

Figure CN118598689B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of surface coating preparation technology, specifically relating to an anti-cyclic ablation zoned coating and its preparation method. Background Technology
[0002] With the continuous development of aerospace vehicles, the development of advanced thermal structural materials for ultra-high temperature conditions has become a research focus in the aerospace field. C / C composites are considered one of the ideal thermal structural materials due to their excellent properties such as low density and stable high-temperature mechanical properties. However, the high-temperature oxidation sensitivity of C / C composites severely limits their application in high-temperature aerobic environments. Surface coating technology, because it can completely isolate oxidizing gases from the matrix material and prevent oxygen from diffusing into the C / C composite, has become an effective means to enable C / C composites to serve for extended periods in high-temperature aerobic environments.
[0003] In recent years, coating technology has been widely studied and applied in the thermal structural components of aerospace vehicles. However, in actual service environments, different regions of thermal structural components experience significant differences in thermal and aerodynamic loads. For example, the leading edge and control wings of aerospace components are most significantly affected by aerodynamic heating, making them prone to stagnation and ablation. The rear end has a lower service temperature but requires reliable connection with heterogeneous structures. The differences in service environments in different regions of the component can lead to uneven deformation of the coating, resulting in significant stress. This can cause the coating to crack or even peel off due to insufficient cohesion, severely affecting its service stability. Reference 1, "Xiaoyang Jiao, Qinchuan He, Qing Tan, et al. Ablation behavior of mullite modified C / C-SiC-HfC composites under oxyacetylene torch for single and cyclic ablations with two heat fluxes[J]. Journal of the European Ceramic Society, 2023, 43(14): 5851-5862," simulates the ablation environment of the sample surface during oxyacetylene flame ablation. It was found that the temperature and gas velocity in the ablation center region of the sample were higher than those in other ablation regions, and both the ablation temperature and gas velocity had a high gradient along the radial direction of the sample. This would lead to a large stress gradient on the sample surface. Reference 2, "Dou Hu, Qiangang Fu, Tianyu Liu, et al. Structural design and ablation performance of ZrB2 / MoSi2 laminated coating for SiC coated carbon / carbon composites[J]. Journal of the European Ceramic Society, 2020, 40(2): 212-219," describes the performance of ZrB2 / MoSi2 coating at 2.4 MW / m². 2 Simulations of temperature and thermal stress after 30 s of ablation under an oxyacetylene flame with a heat flux density revealed that the temperature was highest in the central region of the coating during ablation, but the thermal stress was greatest in the edge region. Furthermore, the thermal stress decreased first and then rapidly increased from the central region to the edge region. This uneven stress distribution led to crack propagation and the formation of large-sized cracks.
[0004] During ablation, a large temperature and flow rate gradient forms on the coating surface, leading to thermal stress due to uneven deformation between different areas. This stress can cause surface cracks to form, propagate, or develop into large cracks, damaging the oxide layer's structure and its ability to block oxygen penetration, and even causing coating failure. Therefore, reducing thermal stress on the coating surface is crucial for improving its protective performance. This necessitates a zoned design of the coating composition based on the size, shape, and service environment characteristics of the thermal structural components to reduce surface stress and enhance the coating's protective capabilities. Summary of the Invention
[0005] The purpose of this invention is to provide an anti-cyclic ablation zoned coating and its preparation method, in order to solve the technical problem of large thermal stress generated in different areas of thermal structural components during service due to uneven deformation.
[0006] To achieve the above objectives, the present invention employs the following technical solution:
[0007] This invention discloses a method for preparing an anti-cyclic ablation zoned coating, comprising the following steps:
[0008] SiC powder, epoxy-modified phenolic resin and anhydrous ethanol were mixed to obtain SiC-phenolic resin slurry.
[0009] Using (Hf,Ta)B2 powder, SiC powder, epoxy-modified phenolic resin and anhydrous ethanol as raw materials, various (Hf,Ta)B2-SiC-phenolic resin slurries with different proportions were prepared.
[0010] A SiC-phenolic resin slurry is applied to the surface of the substrate material and dried to obtain a SiC inner coating. On the surface of the substrate material with the SiC inner coating, the substrate material is divided into zones according to the ablation environment of different areas. Different proportions of (Hf,Ta)B2-SiC-phenolic resin slurry are applied to different zones and dried to obtain (Hf,Ta)B2-SiC zoned coatings.
[0011] The substrate material with (Hf,Ta)B2-SiC partitioned coating is heat-treated to obtain (Hf,Ta)B2-SiC partitioned pre-coating; the substrate material with (Hf,Ta)B2-SiC partitioned pre-coating is subjected to high-temperature vapor phase silicon infiltration treatment to obtain cyclic ablation resistant partitioned coating.
[0012] Furthermore, the specific steps for preparing various (Hf,Ta)B2-SiC-phenolic resin slurries with different proportions using (Hf,Ta)B2 powder, SiC powder, epoxy-modified phenolic resin, and anhydrous ethanol as raw materials are as follows:
[0013] Different proportions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin were weighed and thoroughly stirred with anhydrous ethanol, and then ultrasonically homogenized to obtain various (Hf,Ta)B2-SiC-phenolic resin slurries with different proportions.
[0014] Furthermore, in the SiC-phenolic resin slurry, the mass fraction of SiC powder is 70-85 wt.%, and the mass fraction of epoxy-modified phenolic resin is 15-30 wt.%; the matrix material is a C / C composite material.
[0015] Furthermore, the (Hf,Ta)B2-SiC-phenolic resin slurries with different proportions are of two types, referred to as HT1 slurry and HT2 slurry, respectively;
[0016] In the HT1 slurry, the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin are 60-75 wt.%, 10-20 wt.%, and 15-30 wt.%, respectively.
[0017] Furthermore, in the HT2 slurry, the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin are 25-40 wt.%, 30-60 wt.%, and 15-30 wt.%, respectively.
[0018] Furthermore, the drying temperature is 60-100℃;
[0019] The SiC-phenolic resin slurry is applied 2-3 times; the (Hf,Ta)B2-SiC-phenolic resin slurry with different proportions is applied 6-10 times; the thickness of the SiC inner coating is 50μm; and the thickness of the (Hf,Ta)B2-SiC partitioned coating is 200-250μm.
[0020] Furthermore, the process parameters for the heat treatment are as follows: first, the temperature is raised from room temperature to 100-300℃ and held for 2-5 hours for curing treatment, and then the temperature is raised to 800-1000℃ and held for 2-5 hours for carbonization treatment.
[0021] Furthermore, the process parameters for the high-temperature vapor phase silicon infiltration treatment are as follows: the substrate material with a (Hf,Ta)B2-SiC partitioned pre-coating is placed in a graphite crucible with a silicon block at the bottom, and the temperature is raised from room temperature to 1800-2000℃ in an Ar atmosphere, and then held for 10-40 minutes.
[0022] Furthermore, during the high-temperature vapor phase silicon infiltration treatment, the heating rate from room temperature to 1800-2000℃ is 5-10℃ / min.
[0023] The present invention also discloses an anti-cyclic ablation zoned coating prepared by the above preparation method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] This invention discloses a method for preparing an anti-cyclic ablation partitioned coating. First, a SiC inner coating is prepared on the surface of a substrate material. Then, a (Hf,Ta)B2-SiC partitioned coating is prepared within the SiC inner coating. Subsequently, heat treatment and high-temperature vapor-phase silicon infiltration are performed sequentially, ultimately forming an anti-cyclic ablation partitioned coating ((Hf,Ta)B2-SiC partitioned coating) on the substrate material surface. This method allows for partitioned structure design of the coating on the substrate material surface based on the differences in the service environment of different regions during actual service. Different proportions of (Hf,Ta)B2-SiC-phenolic resin slurry are prepared according to the differences in the service environment of different regions. The resulting anti-cyclic ablation partitioned coating exhibits a gradient change along the radial direction of the substrate material; that is, as the distance from the center of the sample increases, the content of the (Hf,Ta)B2 ceramic phase gradually decreases, while the SiC content gradually increases. This allows for the control of the high-temperature resistance of different regions on the sample surface and effectively alleviates the stress caused by uneven deformation in different regions of the coating, thereby improving the coating's anti-cyclic ablation performance.
[0026] Furthermore, the preparation method of the present invention, after structural design of the coating according to the actual service environment, prepares a partitioned anti-cyclic ablation coating through a combination of slurry coating and high-temperature vapor phase silicon infiltration process. The advantages of this preparation method are as follows: strong designability, not limited by the shape and size of the sample; strong controllability, which can accurately control the size of each region and the composition content and thickness of the coating in each region; it can effectively improve the bonding at the interface of different regions and relieve interface stress; low cost, simple process and short cycle, and has great application prospects in actual production.
[0027] Furthermore, the preparation method of the present invention strictly controls the process parameters such as the heating rate, siliconization temperature and holding time during the high-temperature vapor phase siliconization process, so that the particles in the pre-coating undergo sintering and appropriate rearrangement during the siliconization process to form a gradient coating structure, thereby reducing the thermal stress at the interface between different areas of the coating.
[0028] Furthermore, the preparation method of the present invention can adjust the component content of different areas of the coating according to the actual service environment of different components, and design and prepare a partitioned protective coating suitable for the service environment. This research idea can be extended to the preparation of partitioned coatings on the surfaces of other composite materials, metals and other materials, thereby improving the protective performance of the coating, and has good universality and good application prospects.
[0029] This invention also discloses an anti-cyclic ablation zoned coating obtained by the above preparation method. According to relevant experimental results, this coating can withstand a heat flux density of 4.20 MW / m 2 The coating effectively protects C / C composite material for more than 30s×4 under an oxyacetylene flame. No cracks appeared between the different areas of the coating after ablation, indicating that the bonding between the different areas is good and no thermal mismatch occurred. Moreover, the ablation temperature of the coating surface during cyclic ablation is as high as 2300℃, and the coating remains intact after cyclic ablation with a low ablation loss rate, demonstrating excellent resistance to cyclic ablation. Attached Figure Description
[0030] Figure 1 The flowchart for preparing the anti-cyclic ablation partition of the present invention;
[0031] Figure 2 The XRD pattern of the anti-cyclic ablation partitioned pre-coating prepared in this invention;
[0032] Figure 3 The surface morphology of the anti-cyclic ablation partitioned pre-coating prepared in this invention;
[0033] Figure 4 The XRD pattern and surface morphology of the anti-cyclic ablation partitioned coating prepared in this invention are shown below.
[0034] Where: a-XRD pattern; bd: surface morphology of the zoned coating; e.g.: magnified view of each region in bd;
[0035] Figure 5 The macroscopic surface morphology of the anti-cyclic ablation partitioned coating prepared in this invention after ablation;
[0036] Wherein: a - Example 1; b - Example 2; c - Example 3;
[0037] Figure 6 The image shows the macroscopic surface morphology of the undivided coating after ablation in the comparative example of this invention (comparative example 1). Detailed Implementation
[0038] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0039] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0040] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0041] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0042] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0043] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0044] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0045] Example 1
[0046] A method for preparing an anti-cyclic ablation zoned coating includes the following steps:
[0047] Step 1: Weigh SiC powder and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly and sonicate until there are no obvious agglomerated particles in the slurry, and obtain SiC-phenolic resin slurry; the mass fractions of SiC powder and epoxy-modified phenolic resin in the SiC-phenolic resin slurry are 80 wt.% and 20 wt.% respectively.
[0048] Step 2: Weigh (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly, and sonicate to obtain HT1 slurry; then prepare HT2 slurry using the same preparation steps; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT1 slurry are 64 wt.%, 18 wt.%, and 18 wt.%, respectively; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT2 slurry are 32 wt.%, 50 wt.%, and 18 wt.%, respectively.
[0049] Step 3: Apply SiC-phenolic resin slurry to the cleaned C / C composite material surface with dimensions of Ф30mm×10mm, and dry it in an oven at 70℃. Repeat the above process twice to obtain a SiC inner coating with a thickness of approximately 50μm.
[0050] Step 4: Apply HT1 slurry to the area 0-5 mm from the center of the sample on the surface of the C / C composite material with SiC inner coating, apply HT2 slurry to the area 5-10 mm from the center of the sample, apply SiC-phenolic resin slurry to the area 10-15 mm from the center of the sample, and dry in an oven at 100℃. Repeat the above process 10 times to obtain a (Hf,Ta)B2-SiC partitioned coating with a thickness of 250μm.
[0051] Step 5: Place the above (Hf,Ta)B2-SiC partitioned coating into a tubular heat treatment furnace. First, heat the furnace to 300℃ and hold for 2.5 hours for curing. Then, heat the furnace to 1000℃ and hold for 2 hours for carbonization to obtain (Hf,Ta)B2-SiC partitioned pre-coating.
[0052] Step 6: Place the C / C composite material with (Hf,Ta)B2-SiC partitioned pre-coating into a graphite crucible with a certain amount of silicon block at the bottom, and perform high-temperature vapor phase silicon infiltration treatment in an Ar atmosphere at a heating rate of 5℃ / min and holding at 1800℃ for 15min to obtain the (Hf,Ta)B2-SiC partitioned coating.
[0053] The (Hf,Ta)B2-SiC partitioned coating obtained in this embodiment was applied at a heat flux density of 4.20 MW / m³. 2 After ablation under an oxyacetylene flame for 30 s × 1, the coating surface showed no macroscopic defects, with a mass increase rate of 0.15 mg / s and a thickness increase rate of 0.12 μm / s.
[0054] Example 2
[0055] A method for preparing an anti-cyclic ablation zoned coating includes the following steps:
[0056] Step 1: Weigh SiC powder and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly and sonicate until there are no obvious agglomerated particles in the slurry, and obtain SiC-phenolic resin slurry; the mass fractions of SiC powder and epoxy-modified phenolic resin in the SiC-phenolic resin slurry are 85 wt.% and 15 wt.% respectively.
[0057] Step 2: Weigh (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly, and sonicate to obtain HT1 slurry; then prepare HT2 slurry using the same preparation steps; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT1 slurry are 70 wt.%, 15 wt.%, and 15 wt.%, respectively; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT2 slurry are 25 wt.%, 60 wt.%, and 15 wt.%, respectively.
[0058] Step 3: Apply SiC-phenolic resin slurry to the cleaned C / C composite material surface with dimensions of Ф30mm×10mm, and dry it in an oven at 60℃. Repeat the above process 3 times to obtain a SiC inner coating with a thickness of about 50μm.
[0059] Step 4: Apply HT1 slurry to the area 0-5 mm from the center of the sample on the surface of the C / C composite material with SiC inner coating, apply HT2 slurry to the area 5-10 mm from the center of the sample, apply SiC-phenolic resin slurry to the area 10-15 mm from the center of the sample, and dry in an oven at 70°C. Repeat the above process 6 times to obtain a (Hf,Ta)B2-SiC partitioned coating with a thickness of 200 μm.
[0060] Step 5: Place the above (Hf,Ta)B2-SiC partitioned coating into a tubular heat treatment furnace, first heat it to 100℃ and hold it for 5 hours for curing, then heat it to 1000℃ and hold it for 2.5 hours for carbonization to obtain (Hf,Ta)B2-SiC partitioned pre-coating.
[0061] Step 6: Place the C / C composite material with (Hf,Ta)B2-SiC partitioned pre-coating into a graphite crucible with a certain amount of silicon block at the bottom, and perform high-temperature vapor phase silicon infiltration treatment in an Ar atmosphere at a heating rate of 8℃ / min and holding at 1900℃ for 25min to obtain the (Hf,Ta)B2-SiC partitioned coating.
[0062] The (Hf,Ta)B2-SiC partitioned coating obtained in this embodiment was applied at a heat flux density of 4.20 MW / m³. 2After ablation under an oxyacetylene flame for 30s×2, the coating surface remained intact and dense, without any defects such as cracks. Its mass loss rate was only 0.08mg / s, and its thickness loss rate was 0.12μm / s.
[0063] Example 3
[0064] A method for preparing an anti-cyclic ablation zoned coating includes the following steps:
[0065] Step 1: Weigh SiC powder and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly and sonicate until there are no obvious agglomerated particles in the slurry, and obtain SiC-phenolic resin slurry; the mass fractions of SiC powder and epoxy-modified phenolic resin in SiC-phenolic resin slurry are 77 wt.% and 23 wt.% respectively.
[0066] Step 2: Weigh (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly, and sonicate to obtain HT1 slurry; then prepare HT2 slurry using the same preparation steps; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT1 slurry are 60 wt.%, 10 wt.%, and 30 wt.%, respectively; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT2 slurry are 35 wt.%, 50 wt.%, and 15 wt.%, respectively.
[0067] Step 3: Apply SiC-phenolic resin slurry to the cleaned C / C composite material surface with dimensions of Ф30mm×10mm, and dry it in an oven at 70℃. Repeat the above process 3 times to obtain a SiC inner coating with a thickness of about 50μm.
[0068] Step 4: Apply HT1 slurry to the area 0-5 mm from the center of the sample on the surface of the C / C composite material with SiC inner coating, apply HT2 slurry to the area 5-10 mm from the center of the sample, apply SiC-phenolic resin slurry to the area 10-15 mm from the center of the sample, and dry in an oven at 60°C. Repeat the above process 6 times to obtain a (Hf,Ta)B2-SiC partitioned coating with a thickness of 200 μm.
[0069] Step 5: Place the above (Hf,Ta)B2-SiC partitioned coating into a tubular heat treatment furnace. First, heat the furnace to 300℃ and hold for 2 hours for curing. Then, heat the furnace to 800℃ and hold for 5 hours for carbonization to obtain (Hf,Ta)B2-SiC partitioned pre-coating.
[0070] Step 6: Place the C / C composite material with (Hf,Ta)B2-SiC partitioned pre-coating into a graphite crucible with a certain amount of silicon block at the bottom, and perform high-temperature vapor phase silicon infiltration treatment in an Ar atmosphere at a heating rate of 10℃ / min and a holding temperature of 2000℃ for 30min to obtain the (Hf,Ta)B2-SiC partitioned coating.
[0071] The (Hf,Ta)B2-SiC partitioned coating obtained in this embodiment was applied at a heat flux density of 4.20 MW / m³. 2 After ablation for 30s × 3 under an oxyacetylene flame, no cracking occurred between the regions, and there were no macroscopic defects on the coating surface. The mass loss rate was 0.17 mg / s, and the thickness loss rate was 0.18 μm / s.
[0072] Example 4
[0073] A method for preparing an anti-cyclic ablation zoned coating includes the following steps:
[0074] Step 1: Weigh SiC powder and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly and sonicate until there are no obvious agglomerated particles in the slurry, and obtain SiC-phenolic resin slurry; the mass fractions of SiC powder and epoxy-modified phenolic resin in the SiC-phenolic resin slurry are 70 wt.% and 30 wt.% respectively.
[0075] Step 2: Weigh (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly, and sonicate to obtain HT1 slurry; then prepare HT2 slurry using the same preparation steps; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT1 slurry are 67 wt.%, 15 wt.%, and 18 wt.%, respectively; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT2 slurry are 32 wt.%, 50 wt.%, and 18 wt.%, respectively.
[0076] Step 3: Apply SiC-phenolic resin slurry to the cleaned C / C composite material surface with dimensions of Ф30mm×10mm, and dry it in an oven at 60℃. Repeat the above process 3 times to obtain a SiC inner coating with a thickness of about 50μm.
[0077] Step 4: Apply HT1 slurry to the area 0-5 mm from the center of the sample on the surface of the C / C composite material with SiC inner coating, apply HT2 slurry to the area 5-10 mm from the center of the sample, apply SiC-phenolic resin slurry to the area 10-15 mm from the center of the sample, and dry in an oven at 70°C. Repeat the above process 6 times to obtain a (Hf,Ta)B2-SiC partitioned coating with a thickness of 200 μm.
[0078] Step 5: Place the above (Hf,Ta)B2-SiC partitioned coating into a tubular heat treatment furnace, first heat it to 300℃ and hold it for 4 hours for curing, then heat it to 1000℃ and hold it for 3 hours for carbonization to obtain (Hf,Ta)B2-SiC partitioned pre-coating.
[0079] Step 6: Place the C / C composite material with (Hf,Ta)B2-SiC partitioned pre-coating into a graphite crucible with a certain amount of silicon block at the bottom, and perform high-temperature vapor phase silicon infiltration treatment in an Ar atmosphere at a heating rate of 10℃ / min and holding at 1900℃ for 10min to obtain the (Hf,Ta)B2-SiC partitioned coating.
[0080] The (Hf,Ta)B2-SiC partitioned coating obtained in this embodiment was applied at a heat flux density of 4.20 MW / m³. 2 After ablation for 30 s × 4 under an oxyacetylene flame, its mass loss rate was only 0.62 mg / s and its thickness loss rate was 0.76 μm / s.
[0081] Example 5
[0082] A method for preparing an anti-cyclic ablation zoned coating includes the following steps:
[0083] Step 1: Weigh SiC powder and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly and sonicate until there are no obvious agglomerated particles in the slurry, and obtain SiC-phenolic resin slurry; the mass fractions of SiC powder and epoxy-modified phenolic resin in the SiC-phenolic resin slurry are 70 wt.% and 30 wt.% respectively.
[0084] Step 2: Weigh (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly, and sonicate to obtain HT1 slurry; then prepare HT2 slurry using the same preparation steps; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT1 slurry are 65 wt.%, 20 wt.%, and 15 wt.%, respectively; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT2 slurry are 40 wt.%, 30 wt.%, and 30 wt.%, respectively.
[0085] Step 3: Apply SiC-phenolic resin slurry to the cleaned C / C composite material surface with dimensions of Ф30mm×10mm, and dry it in an oven at 60℃. Repeat the above process 3 times to obtain a SiC inner coating with a thickness of about 50μm.
[0086] Step 4: Apply HT1 slurry to the area 0-5 mm from the center of the sample on the surface of the C / C composite material with SiC inner coating, apply HT2 slurry to the area 5-10 mm from the center of the sample, apply SiC-phenolic resin slurry to the area 10-15 mm from the center of the sample, and dry in an oven at 60°C. Repeat the above process 6 times to obtain a (Hf,Ta)B2-SiC partitioned coating with a thickness of 200 μm.
[0087] Step 5: Place the above (Hf,Ta)B2-SiC partitioned coating into a tubular heat treatment furnace, first heat it to 300℃ and hold it for 5 hours for curing, then heat it to 800℃ and hold it for 5 hours for carbonization to obtain (Hf,Ta)B2-SiC partitioned pre-coating.
[0088] Step 6: Place the C / C composite material with (Hf,Ta)B2-SiC partitioned pre-coating into a graphite crucible with a certain amount of silicon block at the bottom, and perform high-temperature vapor phase silicon infiltration treatment in an Ar atmosphere at a heating rate of 6℃ / min and holding at 1800℃ for 40min to obtain the (Hf,Ta)B2-SiC partitioned coating.
[0089] Example 6
[0090] Step 1: Weigh SiC powder and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly and sonicate until there are no obvious agglomerated particles in the slurry, and obtain SiC-phenolic resin slurry; the mass fractions of SiC powder and epoxy-modified phenolic resin in the SiC-phenolic resin slurry are 70 wt.% and 30 wt.% respectively.
[0091] Step 2: Weigh (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly, and sonicate to obtain HT1 slurry; then prepare HT2 slurry using the same preparation steps; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT1 slurry are 75 wt.%, 10 wt.%, and 15 wt.%, respectively; the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin in HT2 slurry are 25 wt.%, 45 wt.%, and 30 wt.%, respectively.
[0092] Step 3: Apply SiC-phenolic resin slurry to the cleaned C / C composite material surface with dimensions of Ф30mm×10mm, and dry it in an oven at 60℃. Repeat the above process 3 times to obtain a SiC inner coating with a thickness of about 50μm.
[0093] Step 4: Apply HT1 slurry to the area 0-5 mm from the center of the sample on the surface of the C / C composite material with SiC inner coating, apply HT2 slurry to the area 5-10 mm from the center of the sample, apply SiC-phenolic resin slurry to the area 10-15 mm from the center of the sample, and dry in an oven at 60°C. Repeat the above process 8 times to obtain a (Hf,Ta)B2-SiC partitioned coating with a thickness of 230 μm.
[0094] Step 5: Place the above (Hf,Ta)B2-SiC partitioned coating into a tubular heat treatment furnace. First, heat it to 300℃ and hold it for 5 hours for curing. Then, heat it to 900℃ and hold it for 3 hours for carbonization to obtain (Hf,Ta)B2-SiC partitioned pre-coating.
[0095] Step 6: Place the C / C composite material with (Hf,Ta)B2-SiC partitioned pre-coating into a graphite crucible with a certain amount of silicon block at the bottom, and perform high-temperature vapor phase silicon infiltration treatment in an Ar atmosphere at a heating rate of 6℃ / min and holding at 1800℃ for 10min to obtain the (Hf,Ta)B2-SiC partitioned coating.
[0096] Comparative Example 1
[0097] Step 1: Weigh 85 wt.% SiC powder and 15 wt.% epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly and sonicate until there are no obvious agglomerated particles in the slurry, and obtain SiC-phenolic resin slurry.
[0098] Step 2: Weigh 64 wt.% of (Hf,Ta)B2 powder, 18 wt.% of SiC powder and 18 wt.% of epoxy-modified phenolic resin into a beaker, add an appropriate amount of anhydrous ethanol, stir thoroughly and sonicate to obtain HT1 slurry.
[0099] Step 3: Apply SiC-phenolic resin slurry to the cleaned C / C composite material surface with dimensions of Ф30mm×10mm, and dry it in an oven at 70℃. Repeat the above process twice to obtain a SiC inner coating with a thickness of approximately 50μm.
[0100] Step 4: Apply HT1 slurry to the surface of the C / C composite material with SiC inner coating and dry it in an oven at 100℃. Repeat the above process 10 times to obtain a (Hf,Ta)B2-SiC coating with a thickness of 250μm.
[0101] Step 5: Place the above-mentioned coated sample into a tubular heat treatment furnace, first heat it to 200℃ and keep it at that temperature for 2 hours for curing treatment, then heat it to 900℃ and keep it at that temperature for 5 hours for carbonization treatment to obtain (Hf,Ta)B2-SiC pre-coating.
[0102] Step 6: Place the C / C composite material with (Hf,Ta)B2-SiC pre-coating into a graphite crucible with a certain amount of silicon block at the bottom, and perform high-temperature vapor phase silicon infiltration treatment in an Ar atmosphere at a heating rate of 5℃ / min and holding at 1900℃ for 15min to obtain the (Hf,Ta)B2-SiC coating.
[0103] The unpartitioned (Hf,Ta)B2-SiC coating obtained in this embodiment was subjected to a heat flux density of 4.20 MW / m². 2 After ablation for 30 s × 1 under an oxyacetylene flame, the central area of the coating peeled off, and other areas showed obvious cracking, failing to form a complete and dense oxide layer. Furthermore, its mass loss rate was 3.563 mg / s, and its thickness loss rate was 3.983 μm / s, far exceeding the ablation loss rate of the partitioned coating after 30 s.
[0104] Figure 1 The flowchart for preparing the anti-cyclic ablation zone of the present invention illustrates the specific process of preparing the coating of the present invention.
[0105] Figure 2 The image shows the XRD pattern of the anti-cyclic ablation partitioned pre-coating prepared in this invention. As can be seen from the image, the pre-coating is composed of two phases, (Hf,Ta)B2 and SiC, which is consistent with the composition of the original slurry.
[0106] Figure 3The image shows the surface morphology of the anti-cyclic ablation partitioned pre-coating prepared according to the present invention. As can be seen from the figure, the pre-coating is divided into three regions, from left to right: HT1, HT2 and SiC.
[0107] Figure 4 The XRD pattern and surface morphology of the anti-cyclic ablation partitioned coating prepared in this invention are shown in the XRD pattern. It can be seen from the XRD pattern that the coating after high-temperature vapor phase silicon infiltration is composed of three phases: (Hf,Ta)B2, SiC and Si. The surface morphology shows that there are no cracks on the coating surface and no obvious interface between different areas of the coating. The white particles on the coating surface gradually decrease from left to right, showing a gradient change.
[0108] Figure 5 The image shows the macroscopic morphology of the anti-cyclic ablation partitioned coating prepared in this invention after ablation. As can be seen from the image, no cracks appeared between the different regions after the partitioned coating was ablated, indicating that the regions were well bonded and no thermal mismatch occurred.
[0109] Figure 6 The figure shows the macroscopic morphology of the undivided coating after ablation in the comparative example of this invention. As can be seen from the figure, the coating peels off over a large area, and the C / C matrix is exposed in the central area, and the coating loses its protective ability.
[0110] The method of the present invention designs and prepares (Hf,Ta)B2-SiC partitioned coatings according to the ablation environment of different regions of the sample. By adjusting the composition content of different regions of the coating, the high temperature resistance of different regions of the sample surface can be controlled, and the stress caused by uneven deformation in different regions of the coating can be effectively relieved, thereby improving the coating's resistance to cyclic ablation.
[0111] Based on the actual service environment of different components, the composition content of different areas of the coating can be adjusted to design and prepare a zoned protective coating suitable for that service environment. This research approach can be extended to the preparation of zoned coatings on the surfaces of other composite materials, metals, and other materials, thereby improving the protective performance of the coating. It has good universality and broad application prospects.
[0112] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A method for preparing an anti-cyclic ablation zoned coating, characterized in that, Includes the following steps: SiC powder, epoxy-modified phenolic resin and anhydrous ethanol were mixed to obtain SiC-phenolic resin slurry. Using (Hf,Ta)B2 powder, SiC powder, epoxy-modified phenolic resin and anhydrous ethanol as raw materials, various (Hf,Ta)B2-SiC-phenolic resin slurries with different proportions were prepared. A SiC-phenolic resin slurry is applied to the surface of the substrate material and dried to obtain a SiC inner coating. On the surface of the substrate material with the SiC inner coating, the substrate material is divided into zones according to the ablation environment of different areas. Different proportions of (Hf,Ta)B2-SiC-phenolic resin slurry are applied to different zones and dried to obtain (Hf,Ta)B2-SiC zoned coatings. In the SiC-phenolic resin slurry, the mass fraction of SiC powder is 70-85 wt.%, and the mass fraction of epoxy-modified phenolic resin is 15-30 wt.%. The specific steps for preparing various (Hf,Ta)B2-SiC-phenolic resin slurries with different proportions using (Hf,Ta)B2 powder, SiC powder, epoxy-modified phenolic resin, and anhydrous ethanol as raw materials are as follows: Different proportions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin were weighed and thoroughly stirred with anhydrous ethanol, and then ultrasonically homogenized to obtain various (Hf,Ta)B2-SiC-phenolic resin slurries with different proportions. The (Hf,Ta)B2-SiC-phenolic resin slurries with different proportions are of two types, referred to as HT1 slurry and HT2 slurry, respectively. Apply HT1 slurry to the surface of the C / C composite material with SiC inner coating in the area 0-5 mm from the center of the sample, apply HT2 slurry in the area 5-10 mm from the center of the sample, and apply SiC-phenolic resin slurry in the area 10-15 mm from the center of the sample. In the HT1 slurry, the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin are 60-75 wt.%, 10-20 wt.%, and 15-30 wt.%, respectively. In the HT2 slurry, the mass fractions of (Hf,Ta)B2 powder, SiC powder, and epoxy-modified phenolic resin are 25-40 wt.%, 30-60 wt.%, and 15-30 wt.%, respectively. After heat treatment, a substrate material with a (Hf,Ta)B2-SiC partitioned coating is obtained to obtain a (Hf,Ta)B2-SiC partitioned pre-coating. After subjecting the substrate material with (Hf,Ta)B2-SiC partitioned pre-coating to high-temperature vapor phase silicon infiltration treatment, an anti-cyclic ablation partitioned coating is obtained. The drying temperature is 60-100 ℃; The SiC-phenolic resin slurry is applied 2-3 times; the (Hf,Ta)B2-SiC-phenolic resin slurry with different proportions is applied 6-10 times; the thickness of the SiC inner coating is 50 μm; and the thickness of the (Hf,Ta)B2-SiC partitioned coating is 200-250 μm. The process parameters for the high-temperature vapor phase silicon infiltration treatment are as follows: the substrate material with a (Hf,Ta)B2-SiC partitioned pre-coating is placed in a graphite crucible with a silicon block at the bottom, and the temperature is raised from room temperature to 1800-2000 ℃ in an Ar atmosphere, and then held for 10-40 min. The prepared anti-cyclic ablation zoned coating exhibits a gradient change along the radial direction of the substrate material. That is, as the distance from the center of the sample increases, the content of the (Hf, Ta)B2 ceramic phase gradually decreases while the content of SiC gradually increases. This allows for the control of the high-temperature resistance of different regions on the sample surface and effectively alleviates the stress caused by uneven deformation in different regions of the coating, thereby improving the anti-cyclic ablation performance of the coating. This coating can achieve a heat flux density of 4.20 MW / m 2 Effective protection of C / C composite materials under oxyacetylene flame for more than 30 s × 4.
2. The method for preparing an anti-cyclic ablation zoned coating according to claim 1, characterized in that, The heat treatment process parameters are as follows: first, the temperature is raised from room temperature to 100-300 ℃ and held for 2-5 h for curing treatment, then the temperature is raised to 800-1000 ℃ and held for 2-5 h for carbonization treatment.
3. The method for preparing an anti-cyclic ablation zoned coating according to claim 1, characterized in that, During the high-temperature vapor phase silicon infiltration process, the heating rate from room temperature to 1800-2000 ℃ is 5-10 ℃ / min.
4. A zoned coating resistant to cyclic ablation, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 3.
Citation Information
Patent Citations
Preparation method of carbon material surface boride solid solution modified silicon-based coating
CN108218475A
Preparation method of long-time oxidation ablation resistant HfB2-SiC-TaSi2 coating of C / C composite material
CN114874028A
Gradient distribution high-entropy ceramic-SiC modified C / C composite material and preparation method thereof
CN117142870A